Estrategias de intervención psicopedagógica para estudiantes con dislalia del consultorio psicopedagógico de la Universidad Nacional de Chimborazo - Ocaña Martínez, Slendy Nicole (2025)
The objective of the present study was to design a psycho-pedagogical intervention proposal with strategies for managing dyslalia, considering its accessibility and usefulness for parents, teachers, and students, both within and outside the psycho-pedagogical office at the Universidad Nacional de Chimborazo. Dyslalia is a speech disorder that impairs the correct articulation of phonemes, affecting communication and students' comprehensive development. As such, this research emphasizes the importance of addressing the disorder through a comprehensive approach that considers the technical aspects of speech and the emotional and social factors that influence it. The methodology employed was qualitative, using a design based on Grounded Theory. Regarding the types of research: by objective, it was essential; by location, bibliographic; by type of study, cross-sectional; and by level or scope, descriptive and propositional. Accordingly, it is vital to support the research with an extensive bibliographic analysis and gather information from various reliable sources about speech disorders and their intervention strategies. A document analysis matrix was necessary to organize and categorize the collected data, which served as the basis for developing strategies featuring innovative didactic materials and creating a blog to share these resources. In conclusion, the results indicate that dyslalia is a multifactorial disorder that requires personalized treatment. Therefore, practical strategies—such as breathing exercises, articulation activities, and auditory discrimination tasks—are designed to be playful and accessible. Ultimately, these strategies aim to improve students' pronunciation and communication skills, fostering their active participation in the educational process.